Antioxidant action and potential neuroprotection of polyphenolics extracted from Astragalus membranaceus residue - Li, Lu; Wang, Qiaona; Cao, Ying; Li, Jianmei; Wu, Yulong; Hua, Chun; Zhou, Feng; Li, Shengjie; Liu, Su (Frontiers in Nutrition, 2025)
IntroductionPolyphenols, recognized as nutritional supplements, have emerged as promising therapeutic agents for various diseases, particularly brain disorders. However, due to the limitation of the extraction method, Astragalus membranaceus residues (AR) retain substantial bound phenolics with unexplored neuronal antioxidant activity.MethodsIn this study, free, esterified, and bound phenolic compounds were sequentially extracted from AR. Specific compounds in the three phenolic fractions were identified using ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry and categorized into phenolic acids, flavonoids, and isoflavonoids. Antioxidant efficacy was comparatively evaluated through free radical-scavenging assays, ferric reducing antioxidant power assays, and in vitro neuroprotective assessments using PC12 cell models.ResultsThe insoluble-bound fraction had the highest total phenolic content, followed by free and esterified phenolics. Bound phenolic compounds contained the highest amounts of flavonoids. The bound phenolic fraction demonstrated superior comprehensive antioxidant capacity. An in vitro neuroprotective assessment using H2O2-stimulated PC12 neuronal cells demonstrated that the bound phenolic fractions significantly relieved oxidative stress, as evidenced by an increase in superoxide dismutase and catalase and a reduction in intracellular reactive oxygen species and malondialdehyde compared to untreated controls. Bound phenolics in AR also reduced the expression of oxidative stress-related genes in PC12 cells.DiscussionThis study suggests that BP in AR may benefit neurological and brain health as potential nutritional therapies.